Autoimmune Hepatitis Triggered by Anti-TNF-α Therapy. (8th September 2013) - Nakayama, Satoshi
Abstract : Autoimmune hepatitis (AIH) is occasionally triggered by drug treatments. Recently, as biological agents are becoming widely used for autoimmune disorders, there have been a growing number of reports of the development of autoimmune processes related to these agents. A 52-year-old Japanese woman with psoriasis developed liver damage two months after initiation of anti-TNF- α therapy with adalimumab. Liver histological findings were compatible with AIH, and positive conversions of ANAs were detected. The patient was treated with prednisolone and had a good response. While some cases of AIH triggered by anti-TNF- α therapies have been reported, the pathogenesis remains unspecified. When elevation of liver enzymes is observed with high IgG levels and seropositivity of ANA during the course of anti-TNF- α therapy, liver biopsy findings may be essential and important to make definitive diagnosis of AIH.